Perancangan Manajemen Acara Expert Insight Special Episode Marketing Talks “Unlocking Marketing Potential: The Power Of AI” di Telkom Corpu Tahun 2023 - Maharani Dewi, Annisya; Satrio Wijaksono, Dimas (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
Event management plays an important role in the success of an event and should be implemented during its execution, especially for important events such as corporate events. This research was conducted to implement the event management design for the Expert Insight Special Episode Marketing Talks